Acute parotitis in high-dose-rate brachytherapy treatment for skin cancer: a case report - Silvia Rodríguez Villalba; María Pérez-Calatayud; Jose Pérez-Calatayud; Jose Richart Sancho; Manuel Santos Ortega (Journal of Contemporary Brachytherapy, 2021)
Brachytherapy (BT) for skin cancer is an accepted alternative technique, where surgical scars may be of cosmetic concern, or for elderly patients due to significant comorbidity. BT is used for macroscopic disease and as an adjuvant to surgery (after local excision due to positive or close margins or other unfavorable prognostic factors) [1-3]. The objective of this case report was to examine clinical evolution of a patient who unexpectedly developed an acute parotitis, after second adjuvant superficial brachytherapy fraction in the preauricular area. This unusual toxicity has been described in patients receiving external radiotherapy (EBRT) whose parotid gland was included within irradiation volume. After ruling out other causes of unilateral parotitis, clinical evolution, and dosimetric analysis, this reaction was attributed to BT treatment, showing the same known clinical situation but rarely appearing with low-dose external beam treatments. To our knowledge, this unusual toxicity has not been published previously, when BT was employed.